Pengaruh Efisiensi Operasional, Kinerja Investasi, dan Risiko Underwriting terhadap Profitabilitas pada Perusahaan Asuransi yang Terdaftar di BEI Periode 2021–2024 - Widya Ayu Pratiwi; Dian Ayu Andriani (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study is motivated by the growing need to understand the determinants of profitability in the insurance subsector, particularly in the context of increasing competition and financial performance pressures. It aims to examine the partial and simultaneous effects of BOPO, Return on Investment (ROI), and Loss Ratio on profitability. The population consists of insurance companies listed on the Indonesia Stock Exchange (IDX), with a purposive sampling method resulting in 10 companies observed over the 2021–2024 period. From 40 initial observations, 8 outliers were excluded, leaving 32 samples for analysis. The study employs multiple linear regression using statistical software to test the hypotheses. The findings reveal that ROI has a significant positive effect on profitability, indicating that effective investment management plays a crucial role in enhancing financial performance. Meanwhile, BOPO and Loss Ratio do not show significant partial effects, suggesting that operational efficiency and risk outcomes alone are insufficient to drive profitability. However, collectively, these variables still contribute to explaining profitability, although with moderate explanatory power. This implies the presence of other influential factors, such as market dynamics and managerial decisions.